“Proyecto de Factibilidad para la implementación de una empresa productora y distribuidora de licor de ovo en la ciudad de Ibarra, provincia de Imbabura” - Villegas Chavarrea, Pablo Francisco (2024)
The present project seeks to elaborate a liqueur produced from an exotic fruit, very particular to the area of Ambuquí in the province of Imbabura. This fruit known as Ovo has unique characteristics that make it very special and desired to be the main ingredient in a great variety of products. One of the disadvantages of this fruit is its rapid maturation after its harvest, which makes it impossible to distribute it to different cities outside the province, in this aspect the development of a product based on Ovo, in this case a liqueur, is an alternative for the flavor and aromas of this fruit, to be known in other sectors of our country. At the beginning of this project, a general objective was created: To elaborate a Feasibility Project for the Implementation of an Egg Liqueur Production and Distribution Company in the city of Ibarra, Province of Imbabura, as well as the specific objectives that served as support and guide for the development of the project. With the definition of the main objective, we proceeded to develop the project with the use of methods, techniques and procedures that allowed the study to have the necessary authenticity. Among the methods used we have the deductive method, which allowed us to reach logical and coherent conclusions from concrete indications, it was also used to analyze the feasibility and profitability of the project through the application of established principles and rules. Likewise, the inductive method was used to analyze concrete data and specific observations in order to reach general conclusions, so the first step was to gather relevant information on the market, the technical and financial feasibility of the project, among other key aspects. In the same way, different techniques were applied, such as the survey, which focused on knowing the preferences of the new product. Interviews were also conducted to learn about some 6 processes, including liquor production, necessary inputs, machinery, among others. And finally, direct observation was used to approach the process of planting, harvesting and marketing of the fruit. To establish the demand, supply and unsatisfied demand of Ovo liquor, a sample of the EAP (Economically Active People) of the Ibarra city was taken, being this the amount of 97,094 people, giving a total of 398 surveys. For the study and analysis of supply, a survey was conducted of commercial establishments that sell alcoholic beverages, in this case liquor stores registered in the municipal police station of the city of Ibarra, with a universe of 78 establishments, resulting in a survey of 65 of these establishments. Thus, the analysis carried out in the development of each of the phases of the feasibility project led to the following conclusions: The Market Study determines that the company is feasible to start up. According to the data obtained, there is an unsatisfied demand of 298,829 liters of liquor for the first year. The installed capacity will cover 18% of the unsatisfied demand, that is, 54,750 liters. The investment amounts to $ 116.577,12 dollars, of which 75% will be external capital and 25% equity; the break-even analysis showed that for the first year the company should use an installed capacity of 43,7% and should have sales of $ 107.701,47 so that the company neither wins nor loses. The financial evaluation indicates that the VAN is $ 67.196,87, an TIR of 24,72%, that the company will recover the capital in 4 years, 2 months and 15 days; that for every dollar invested the company earns $ 1,24 cents, the company, in terms of price variation, fixed cost and variable 7 cost, complies with the price and cost awareness analysis, determining that the implementation of this type of company is feasible in the city of Ibarra, province of Imbabura. Thus, based on the results obtained, it is recommended that the project be implemented since it will provide significant profitability for its owners and investors, in addition to generating sources of employment and contributing to the productive and economic development of the Ibarra city.